Carbon Stock in Plantations Of Juglans Neotropica Diels, with And without Associate of Coffea Arabica L. - Ramírez López, Jorge Luis (2019)
The objective of the research was to estimate the carbon stock in plantations and agroforestry systems of neotropic Juglans neotropica in the northern Ecuadorian highlands, as a contribution to climate change adaptation and mitigation strategies. Carbon was estimated from two 20-year-old plantations of Juglans neotropica, one pure and one in association with Coffea arabica. The biomass of trees and detritus is determined by the relationship between fresh and dry matter. With a factor of 0.5 the biomass is transformed into carbon and allometric formulas were made to determine the total carbon of the plantation. Detritus carbon was determined in the laboratory and extrapolated to the surface unit. The carbon stock by the pure plantation was 13.17 Mg ha-1, while in association it was 16.11 Mg ha-1. Differences in the carbon content of all components were observed, with the bole being the component that stock the most carbon. Detritus were the component that had the greatest differences between the systems. It is concluded that the plantation in association stock greater amount of carbon, which shows that the inclusion of coffee favors the growth and production of biomass of J. neotropica. The bole was the component of greater storage, fact that contributed to the linear relationship with the DAP2Ht regressor, obtaining equations with more than a 90% adjustment that allows estimating the carbon stored in silvicultural and edaphoclimatic conditions similar to those of the study.